A versatile, cost-effective, and flexible wearable biosensor for in situ and ex situ sweat analysis, and personalized nutrition assessment. Issue 20 (9th September 2019) - Zhang, Zhong; Azizi, Morteza; Lee, Michelle; Davidowsky, Philip; Lawrence, Peter; Abbaspourrad, Alireza
Abstract : Point-of-care (POC) diagnostics have shown excellent potential in rapid biological analysis and health/disease monitoring. Abstract : Point-of-care (POC) diagnostics have shown excellent potential in rapid biological analysis and health/disease monitoring. Here, we introduce a versatile, cost-effective, flexible, and wearable POC biomarker patch for effective sweat collection and health monitoring. We design and fabricate channels/patterns on filter paper using wax printing technology, which can direct sweat to collection and biomarker detection zones on the proposed platform. The detection zones are designed to measure the amount of collected sweat, in addition to measuring the sweat pH, and glucose (a potential diabetic biomarker), and lactate concentrations. It is significantly challenging to measure glucose in human sweat by colorimetric methods due to the extremely low glucose levels found in this medium. However, we overcame this issue by effectively engineering our wearable biosensor for optimal intake, storage, and evaporation of sweat. Our design concentrates the colorant (indicator) into a small detection zone and significantly increases the sensitivity for the sweat glucose sensing reactions. The device can thus detect glucose in physiological glucose concentration range of 50–300 μM. This cost-effective and wearable biosensor can provide instant in situ quantitative results for targets of interest, such as glucose, pH, and lactate, when coupled with the imaging and computing functionalities of smartphones. Meanwhile, it is also feasible to extract the air-dried sweat from the storage zone for further ex situ measurements of a broader portfolio of biomarkers, leading to applications of our wearable biosensor in personalized nutrition and medicine.